(untitled) (Papeles, 2023)
To analyse women’s political participation is necessary to focus on processes of political expansion and the answers given or the limits created by patriarchal structures. Analysing women’s political engagement requires concentrating on political growth processes and the solutions or limitations imposed by patriarchal systems. The last decade of the 20th Century and the first two decades of the 21st century demonstrate how crucial the implementation of legislation to enhance and strengthen the presence of women in public and political decision-making spaces has been. Laws, like the parity law today and the quotas in the 1990s, attempt to balance and modify this asymmetric reality. As a result, this dissertation examines the gender electoral changes in Argentina and the province of Santa Fe, concentrating on the political strategies developed for its legislative approval. It also takes into account what the difficulties of the future will be.